Restorative Approach Creates Child Friendly School Free of Bullying - Nur Fatihah; Nur Aisyah; Uthman Shehu Lawal (Journal of Psychological Insight, 2025)
Bullying remains a critical challenge in schools, affecting students’ psychological well-being and social development. This study aims to examine the effectiveness of the restorative approach in fostering anti-bullying behavior by enhancing empathy, responsibility, and social skills among students. Using a qualitative methodology, data were collected through observations, interviews, and focus group discussions involving students, teachers, and counselors. The findings indicate that restorative dialogue and mediation significantly reduced conflicts, increased students’ awareness of the impact of their actions, and promoted positive behavioral changes among perpetrators. Victims reported feeling acknowledged and supported, while overall classroom interactions improved. This study contributes to the understanding of how restorative practices can transform school culture by prioritizing relationship restoration over punitive measures. The results suggest that implementing restorative approaches can effectively reduce bullying, enhance social-emotional skills, and support the development of an inclusive, child-friendly educational environment, offering practical guidance for educators and school policymakers.